2014
DOI: 10.1158/1535-7163.mct-13-0560-t
|View full text |Cite
|
Sign up to set email alerts
|

GSK3 Inhibitors Regulate MYCN mRNA Levels and Reduce Neuroblastoma Cell Viability through Multiple Mechanisms, Including p53 and Wnt Signaling

Abstract: Neuroblastoma is an embryonal tumor accounting for approximately 15% of childhood cancer deaths. There exists a clinical need to identify novel therapeutic targets, particularly for treatment-resistant forms of neuroblastoma. Therefore, we investigated the role of the neuronal master regulator GSK3 in controlling neuroblastoma cell fate. We identified novel GSK3-mediated regulation of MYC (c-MYC and MYCN) mRNA levels, which may have implications for numerous MYC-driven cancers. In addition, we showed that cert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(104 citation statements)
references
References 53 publications
7
95
1
1
Order By: Relevance
“…4G). Given that Wnt signalling has been shown to confer the apoptotic effect of some GSK3 inhibitor in cancer cells [45], these results indicated that GSK3 inhibition is synthetic lethal with p53 re-activation, possibly through its effect on the action of Wnt signalling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4G). Given that Wnt signalling has been shown to confer the apoptotic effect of some GSK3 inhibitor in cancer cells [45], these results indicated that GSK3 inhibition is synthetic lethal with p53 re-activation, possibly through its effect on the action of Wnt signalling.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is hard to identify the factor conferring the synthetic lethal effect of GSK3 inhibition and p53 re-activation based on our current findings. Additionally, Wnt signalling has been shown to be important for the apoptotic effect of some GSK3 inhibitor in cancer cells [45], since GSK3 is a key kinase repressing Wnt signalling pathway through mediating β-catenin phosphorylation and subsequent degradation [44]. In present study, we found that the transcriptional activity of β-catenin induced by SB216763 was much lower than those induced by other inhibitors, although the transcriptional activity of β-catenin was enhanced by all these four inhibitors (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, GSK3β and Wnt/Axin2 coordinately regulate β-catenin-TCF to control tumor proliferation and metastasis in breast cancer [34]. Wnt pathway is reported as downstream target of GSK3β in controlling neuroblastoma growth [35]. In addition, although not investigated for cancer, GSK3β directly induces the expression of Bax1 in an ischemic injury model [36].…”
Section: Discussionmentioning
confidence: 99%
“…The RNA extraction, DNA digestion, quality control, sequencing and bioinformatics were performed as previously described on an Illumina GA IIx [19]. The aligned data are publically available in ArrayExpress under the accession number E-MTAB-2691.…”
Section: Methodsmentioning
confidence: 99%